The impact of intense and repeated exposure to immoral content on social values ​​and behavior: An analytical study of closed feminist groups on Facebook (The International Journal of Educational Sciences and Arts, 2025)
This analytical study examines the effects of intensive and continuous exposure to unethical content on the values and behaviors of young women, with a focus on closed feminist groups on Facebook. The paper draws on a mix of Arabic and international literature, alongside recent field studies, to highlight manifestations of the normalization of controversial discourse, the transformation of moral standards, and the internal conflict between inherited values and peer pressure in digital spaces.The research adopted a mixed-approaches approach, combining quantitative and qualitative content analysis, along with an electronic survey, which included 1,000 female participants and in-depth interviews with 25 female participants. The results revealed that a statistically significant positive correlation between exposure intensity and the normalization of behaviors, which is, contradict prevailing values, as well as increased levels of social anxiety and internal value conflict. The study recommends adopting digital media literacy programs, supportive positive content, and enhancing the role of families and educational institutions in reinforcing ethical values.
Keywords: Unethical Content; Facebook; Closed Groups; Moral Values; Youth; Girls; Women; Normalization; Digital Culture